2021
DOI: 10.3390/antiox10050776
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin and Luteolin Regulate Autophagy by Targeting NRH-Quinone Oxidoreductase 2 in Liver Cells

Abstract: Dietary flavonoids stimulate autophagy and prevent liver dysfunction, but the upstream signaling pathways triggered by these compounds are not well understood. Certain polyphenols bind directly to NRH-quinone oxidoreductase 2 (NQO2) and inhibit its activity. NQO2 is highly expressed in the liver, where it participates in quinone metabolism, but recent evidence indicates that it may also play a role in the regulation of oxidative stress and autophagy. Here, we addressed a potential role of NQO2 in autophagy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…It has previously been observed that reduction of the flavin cosubstrate and binding of chloroquine resulted in a change in conformation or dynamics, which could affect interactions of NQO2 with other molecules ( Leung and Shilton, 2013 ). A recent manuscript implicating NQO2 in regulation of autophagy concluded that the mechanism may not require catalytic activity, but instead depend on signaling through ligand binding and changes in protein-protein interactions ( Janda et al, 2021 ). Another possibility is that NQO2 signals through the production of reactive oxygen species, which have been detected in vitro ( Reybier et al, 2011 ) and in cells ( Cassagnes et al, 2015 ) during the reduction of quinones by NQO2 using a suitable cosubstrate such as NRH or BNAH.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been observed that reduction of the flavin cosubstrate and binding of chloroquine resulted in a change in conformation or dynamics, which could affect interactions of NQO2 with other molecules ( Leung and Shilton, 2013 ). A recent manuscript implicating NQO2 in regulation of autophagy concluded that the mechanism may not require catalytic activity, but instead depend on signaling through ligand binding and changes in protein-protein interactions ( Janda et al, 2021 ). Another possibility is that NQO2 signals through the production of reactive oxygen species, which have been detected in vitro ( Reybier et al, 2011 ) and in cells ( Cassagnes et al, 2015 ) during the reduction of quinones by NQO2 using a suitable cosubstrate such as NRH or BNAH.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, S29434 by acting as a protective agent on astrocytes, might delay neuronal damages in PD and other pathological conditions concerning OS and autophagy impairment mediated by NQO2, suggesting that NQO2 inhibitors might have a therapeutic potential for the treatment of cerebral injuries involving oxidative neurodegeneration. The vast literature suggesting a protective effect of several natural polyphenols in neurodegeneration strongly supports this idea, since NQO2 is a well-documented target of these compounds [39,64]. Future studies should validate this hypothesis.…”
Section: Figurementioning
confidence: 90%
“…Overall, due to the reported speci city of S29434 towards NQO2 [38], these and our previous data strongly suggest that NQO2 is an important modulator of autophagy. The question whether it is due to the enzymatic activity of NQO2 or to the formation of NQO2 complexes with protein partners hypothetically regulated by S29434 and other inhibitors, as suggested previously [39], is not yet clear.…”
Section: Figurementioning
confidence: 91%
See 2 more Smart Citations